The role of a spatial-temporal deictic paradigm in literary analysis : an evaluation of Karel Schoeman's triptych "Stemme” ['Voices'] - Claassen, Joel (Afrikaans and Netherlandic Studies, 2014)
Deixis has had a useful, yet fairly one-dimensional history in Linguistics. The core of traditional deixis is essentially the manner that the utterance reflects the spatial and temporal position of the narrator. The aim of this study has been to pursue a paradigmatic application of deixis to literature, much as Snyman (1983), Anker (1987) and Fludernik (1997) have utilised deixis as a stylistic tool in the analysis of poetry, short stories and shorter novels. What this dissertation proposes is that deixis could also be a viewed as a literary paradigm in the analysis of literary texts. The deictic paradigm can also be especially important, as a narrative structural principle, in the evaluation of literary texts where space and time causes particular difficulty. In order to develop deixis as a paradigm, a spatial and temporal deictic analysis, is emphasized.